EFFICIENCY OF RAW MILK PROCESSING IN RANGE OF DAIRY PRODUCTS DEPENDING ON ITS BREED - Рыжкова, Т. Н.; Гончарова, И. И.; Гейда, И. Н. (Scientific Progress & Innovations, 2014)
This article provides comparative data of the research results of milk samples of two groups of Ukrainian black-pied and Ukrainian red-pied breeds of cows which are kept in the educational and research center of Kharkov State Zooveterinary Academy to choose the optimal flow sheet of its processing on prepared dairy products. The milk which is given by the Ukrainian red-pied cows is expediently processed into rennet cheese, is given by Ukrainian black-pied cows should be directed for the production of whole-milk dairy products.